A prospective randomized controlled trial comparing infliximab and etanercept in patients with moderate‐to‐severe chronic plaque‐type psoriasis: the Psoriasis Infliximab vs. Etanercept Comparison Evaluation (PIECE) study. (1st March 2017) - de Vries, A.C.Q.; Thio, H.B.; de Kort, W.J.A.; Opmeer, B.C.; van der Stok, H.M.; de Jong, E.M.G.J.; Horvath, B.; Busschbach, J.J.V.; Nijsten, T.E.C.; Spuls, Ph.I.
Summary: Background: There are currently no independent data available comparing infliximab and etanercept for the treatment of psoriasis. Objectives: To compare these biologics without funding from pharmaceutical companies. Methods: Overall, 50 patients were randomized to etanercept ( n = 23) 50 mg subcutaneously twice weekly or infliximab ( n = 25) 5 mg kg −1 intravenously at week 0, 2, 6, 14 and 22. After 24 weeks, 19 patients stopped and 22 continued treatment and were followed up to week 48. The primary outcome was ≥ 75% improvement of Psoriasis Area and Severity Index (PASI 75) at week 24. The secondary outcomes included PASI 75 at week 6 (onset of action) and week 12, Investigator's Global Assessment (IGA), Patient Global Assessment, impact on quality of life (Skindex‐17 and SF‐36), Treatment Satisfaction Questionnaire of Medication, duration of remission, maintenance treatment and safety. Results: At week 24, PASI 75 was achieved in 72% (infliximab) vs. 35% (etanercept) ( P = 0·01). The onset of action was achieved in 52% (infliximab) and 4% (etanercept). At week 12, 76% (infliximab) and 22% (etanercept) achieved PASI 75 ( P < 0·001). At week 24, IGA 'clear or almost clear' was observed in 76% (infliximab) and 30% (etanercept) ( P = 0·01). Skindex‐17 symptom score was significantly better for infliximab. Maintenance treatment achieved PASI 75 for 67% ( n = 6) infliximab vs. 50% ( n = 5) etanercept, at week 48 ( P = 0·65). Mild adverse events were reported in 76% (infliximab) vs. 66% (etanercept). Conclusions: Infliximab showed a rapid and significant higher level of efficacy until week 24 compared with etanercept. Long‐term data showed no significant differences between both groups at week 48. Safety parameters were comparable.